THE DEVELOPMENT OF ELECTRONIC EDUCATIO0NAL RESOURCES FOR A DISCIPLINE - Olga V. Chudina; Andrey V. Ostroukh (Moscow Polytechnic University, 2016)
The article is devoted to the development of e-learning resource for a discipline «Material science» in order to visualize complex latent processes in the metals during the heat treatment. In the article the technologies of the development of software environment are described. Using concrete examples it was shown how the application of multimedia learning tools in the educational process increases the efficiency of the teaching during lectures, practical training and facilitates assimilation of the material by students during their self-dependent work.